2015
DOI: 10.1021/acs.orglett.5b01221
|View full text |Cite
|
Sign up to set email alerts
|

Sulfenylation of β-Diketones Using C–HFunctionalization Strategy

Abstract: Sulfenylation of β-diketones is challenging as β-diketones undergo deacylation after sulfenylation in the reaction medium. The sulfenylation of β-diketones without deacylation under metal-free conditions at ambient temperature via a cross dehydrogenative coupling (CDC) strategy is reported. The resultant products can be further manipulated to form α,α-disubstituted β-diketones and pyrazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Commercial NaH is supplied in a relatively safe form of 60% dispersion in mineral oil. Although other researchers recommended to use this dispersion in native form [1819 25], we have found that mineral oil should be removed before the synthesis. The results of the optimization experiments are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Commercial NaH is supplied in a relatively safe form of 60% dispersion in mineral oil. Although other researchers recommended to use this dispersion in native form [1819 25], we have found that mineral oil should be removed before the synthesis. The results of the optimization experiments are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 96%
“…It was found that mixing 2-acetylthiophene with a base in the absence of the ester (var. A) should be avoided due to notable darkening and self-condensation of the ketone, despite Prabhu’s recommendations [25]. Similar yields of a β-diketone were obtained if the ester of perfluorocarboxylic acid was first added to a base (var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] We commenced our studies by examining the reaction between indolin-2-one (1 a) and 4-chlorobenzenethiol (2 a) in the presence of a catalytic amount of iron salts (10 mol%) [3][4][5][6][7][8]. It was found that all the tested iron salts could drive the reaction, and FeCl 3 was shown the best efficiency to afford the [9][10][11][12]. The loading of the base was also optimized (entries 13 and 14).…”
Section: Resultsmentioning
confidence: 99%
“…The cross-dehydrogenative coupling (CDC) is one of the most straightforward and efficient approache in organic synthesis due to its high atom and step economy, avoiding prefunctionalization of starting materials. [8] However, the CDC methods for C(sp 3 )À X (S/Se) bonds construction are relatively less explored, [9] and many of them suffered limitations including typical substrates, strong oxidants and harsh reaction conditions. The development of a green and mild strategy leading to C(sp 3 )À X (S/Se) bonds formation is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%